9 and 13
You can set this up as follows:
Let A be the first number
Let B be the second number
Two equations:
A + B = 22 (sum is 22)
A - B = 4 (difference is 4)
Now use one of the equation (I'll use the second equation) to solve for one of the variables (I'll pick A)
A - B = 4
A = B + 4
Now plug this value of A into the first equation.
A + B = 22
(B+4) + B = 22
2B + 4 = 22
2B = 18
B = 9
Then just plug B back into one of the equations to solve for A:
A + 9 = 22
A = 22 - 9
A = 13
So the two numbers are 13 and 9.
13 + 9 = 22
13 - 9 = 4
2006-10-11 09:38:54
·
answer #1
·
answered by Puzzling 7
·
0⤊
0⤋
9 and 13
2006-10-11 20:27:49
·
answer #2
·
answered by spens 2
·
0⤊
0⤋
the anser is 13 and 9 there is a 4 number diffrence and thye equal 22 in the end to
2006-10-11 16:44:56
·
answer #3
·
answered by hotchick_8587 2
·
0⤊
0⤋
9 & 13
2006-10-11 16:40:51
·
answer #4
·
answered by Young Mother 1
·
0⤊
0⤋
It's 9 and 13 guaranteed.
2006-10-11 16:44:56
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
9 and 13.
(Let us have two numbers, say x and y.
Two numbers have asum of 22.
It means,
x+y=22...............(1)
Their difference is 4.
It means,
x-y=4...............(2)
from 2, we have,
x=4+y
placing above value in eq.2,we have,
4+y+y=22
2y=22-4
2y=18
y=18/2
y=9.
Put y=9 in , eq.2,we have,
x-9=4
x=4+9
x=13.)
2006-10-11 16:46:31
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
x + (x+4)=22
2x = 18
x = 9
x +4 =13
2006-10-11 16:47:14
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
a+b= 22
a-b=4
2a=26
a=13
b=9
2006-10-11 16:40:43
·
answer #8
·
answered by Gina7 1
·
0⤊
0⤋